Correlation analysis of lipid accumulation index, triglyceride-glucose index and H-type hypertension and coronary artery disease - Yuan,Wenwen; Shao,Yan; Zhao,Dong; Zhang,Bin (PeerJ, 2023)
Objective The current research was designed to explore the relationship between the lipid accumulation index (LAP), coronary artery disease (CAD), and the triglyceride-glucose (TyG) index in patient with H-type hypertension. Methods From June 2021 to January 2022, our hospital’s information management system collected data on 186 patients with essential hypertension. The participants were categorized into two groups (H-type hypertension (n = 113) and non-H-type hypertension (n = 73)) based on their homocysteine levels. Both groups’ general condition, lipid accumulation index, triglyceride-glucose index, and Gensini score were compared to determine the factors influencing the severity of CAD in H-type hypertension patients. Results There were statistically significant differences (P < 0.05) in homocysteine (Hcy, GLP-1 and SAA) level, LAP, and TyG indexes, but not in body mass index (BMI), smoking, sex, age, total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C), fasting plasma glucose (FPG), diastolic blood pressure, and systolic blood pressure. Additionally, there were substantial variations between the two groups regarding the number of lesion branches, degree of stenosis, and Gensini score (P > 0.05). patient with grade III to IV lesions had substantially higher LAP and TyG indices than those with stage I to II (P < 0.05). TyG (OR = 2.687) and TyG-LAP (OR = 4.512) were the factors determining the incidence of coronary artery disease in H-type hypertension, according to multivariate logistic regression analysis. The lesion number, stenosis degree, and Gensini score (P < 0.05) varied among both groups. LAP and TyG indexes were substantially greater in patients with double and triple vessel lesions than in those without lesions or with single vessel lesions (P < 0.05); similarly, these two indexes were considerably higher in individuals with grade III to IV lesions than in patients with grade I to II lesions (P < 0.05). As per the Pearson correlation analysis, the LAP, TyG indices and SAAlevel were adversely connected to the Gensini score (r = 0.254, 0.262, 0.299, P < 0.05), the GLP-1 level was negatively correlated to the Gensini score (r = −0.291, P < 0.05). TyG (OR = 2.687) and TyG-LAP (OR = 4.512) were the factors determining the frequency of coronary artery disease in H-type hypertension, according to multivariate logistic regression analysis. Conclusion In conclusion, the LAP and TyG indexes were observed to be closely related to the degree of CAD in H-type individuals with hypertension, which can better understand the pathogenesis of coronary artery disease in patients with H-type hypertension and is of great significance for guiding clinical doctors to carry out personalized treatment and management.
Keywords: Lipid accumulation index; Triglyceride-glucose index; H-type hypertension; Coronary artery disease